2021
DOI: 10.3390/w13141910
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Long-Term Dynamics of Zooplankton in the Ob River on Interannual Changes in Hydrological and Hydrochemical Parameters

Abstract: Here we summarize a long-term study on qualitative and quantitative composition of zooplankton (Cladocera, Copepoda, Rotifera) in the Ob River. We carried out these investigations at 13 sampling stations of the Middle and Low Ob in the years 1994, 1996, 1999, 2001, 2002 and 2009. It was found that the species richness of all zooplankton and abundance of cladocerans and rotifers is significantly determined by the temperature conditions of the month preceding sampling. In contrast, among other factors, we reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Essien-Ibok and Ekpo [59] found that the highest zooplankton density coincides with the high values of phosphate and nitrates. Also, Yermolaeva et al [60] showed that increasing phosphates and nitrates stimulate the growth of rotifera and cladocera in Ob River western of Siberia.…”
Section: Nitrate (No3 -)mentioning
confidence: 99%
“…Essien-Ibok and Ekpo [59] found that the highest zooplankton density coincides with the high values of phosphate and nitrates. Also, Yermolaeva et al [60] showed that increasing phosphates and nitrates stimulate the growth of rotifera and cladocera in Ob River western of Siberia.…”
Section: Nitrate (No3 -)mentioning
confidence: 99%
“…The hydrochemical characteristics of rivers could influence the growth of zooplankton. To investigate this influence, Yermolaeva et al [6] performed a long-term experiment for the composition of zooplankton in the Ob River, Russia, in the years 1994, 1996, 1999, 2001, 2002, and 2009. This experiment found that species richness and abundance were closely related to the temperature in the month before sampling; PH had a negative correlation, while phosphate and nitrate concentrations had a positive correlation with zooplankton abundance.…”
Section: Interaction Between Environmental and Ecological Processesmentioning
confidence: 99%
“…The total length of the river is 3,680 km. With respect to the nature of the valley and watercourse, the river is conventionally divided into 3 parts: the upper part stretches from the confluence of the Biya and the Katun to the Tom mouth (1,020 km), the middle part stretches from the Tom to the Irtysh mouth (1,500 km), and the lower part stretches from the Irtysh mouth to the Ob Bay (1,160 km) (Plaschev and Chekmarev 1967;Mitrofanova 2019;Yermolaeva et al 2021).…”
Section: Introductionmentioning
confidence: 99%